Harmonising food safety and friendly service through halal and toyyib principles - Md Dahlal, Norazilawati; Che Noh, Che NurHidayu; Mohamed Saniff, Shereeza (IIUM Press, 2024)
The widespread problem of food poisoning poses a serious threat to public health, with potentially severe consequences, including death. Food vendors need to prioritize offering halal and safe, flavorful food, ensuring excellent taste and service quality for consumers. This paper explores implementing food safety and friendly services aligned with halal and toyyib principles to address food safety and quality issues effectively. These principles include the physical characteristics of the product in accordance with Shari’ah law (P1); products that are sourced ethically and responsibly (P2); products that meet high standards of quality and safety (P3); functioning as servant and caliph of Allah in managing according to Allah's commands and prohibitions (P4); not excessively wasteful or extravagant (P5); positive moral and spiritual implications associated with the product (P6); and aimed at achieving prosperity in both this life and the hereafter (P7). This review article delves into how widespread and consequential it is to establish a structure for ensuring food safety and quality in the halal industry. By closely examining the halal and toyyib principles in the food sector, it becomes clear that grasping the importance of each principle is crucial for upholding the utmost standards in the halal and toyyib food sectors.